Poly (vinylidene fluoride-co-hexafluoro propylene) / polyethylene oxide-based nanoparticles reinforced gel polymer electrolytes for dye-sensitized solar cell / Negar Zebardastan - Negar , Zebardastan (2017)
Solar energy is the most abundant and clean source of energy on the earth. Recently scientists have been able to develop a technology to harvest solar energy and today we are able to convert the sunlight directly to the electricity. Dye-sensitized solar cells (DSSCs) are one of the promising solar harvesting technologies with numerous advantages over the other technologies such as silicon based solar cells. Usually high performance DSSCs are obtained using liquid electrolyte which face several drawbacks for long term usage, such as leakage, electrolyte evaporation and interface corrosion. Gel polymer electrolyte can be an alternative to overcome these issues but the ionic conductivity of this gel polymer electrolytes must be improved to achieve high energy conversion efficiency. In this work we studied three gel polymer electrolyte (GPE) systems and the performance of DSSCs using GPEs have been analyzed. These GPEs are formulated by blending Poly(vinylidene fluoride-co-hexafluoro propylene) copolymer (PVdF-HFP) and polyethylene oxide (PEO) polymers. First, incorporation of sodium iodide (NaI) salt in different concentrations in the GPE system is investigated and later the addition of fumed silica (SiO2) and zinc oxide (ZnO) nanofiller into the GPE system are studied. GPEs are examined using electrochemical impedance spectroscopy (EIS) to determine ionic conductivity values. The highest ionic conductivities of 6.38, 8.84 and 8.36 mS cm−1 are achieved after the incorporation of 100 wt.% of sodium iodide (NaI), 13 wt.% of fumed silica (SiO2) and 3 wt.% of ZnO in each system, respectively. Temperature-dependent ionic conductivity study confirms that GPE systems follow Arrhenius thermal activated model. GPEs are characterized for structural studies using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. DSSCs are fabricated using GPEs and need to be recorded under 1 Sun simulator which produced the significant highest energy conversion efficiency of 5.67, 9.44 and 9.08 % with incorporation of 100 wt.% of sodium iodide (NaI) with respect to the total weight of PEO:PVdF-HFP polymers, 13 wt.% of fumed silica (SiO2) and 3 wt.% of ZnO in each system, respectively.